'Billings' Wheat Combines Early Maturity, Disease Resistance, and Desirable Grain Quality for the Southern Great Plains, USA. Issue 1 (4th October 2013) - Hunger, Robert M.; Edwards, Jeffrey T.; Bowden, Robert L.; Yan, Liuling; Rayas-Duarte, Patricia; Bai, Guihua; Horn, Gerald W.; Kolmer, James A.; Giles, Kris L.; Chen, Ming-Shun; Jin, Yue; Osburn, Roger D.; et al.
Abstract : Selection pressure for earliness, resistance to multiple pathogens, and quality attributes consistent with the hard red winter (HRW) wheat ( Triticum aestivum L.) market class is tantamount to, or can obscure, selection for yield potential in lower elevations of the U.S. southern Great Plains. The decline in acreage of 'Jagger' (PI 593688) only impelled this inclination as producers searched for substitutes in the Jagger maturity and yield range but with improved disease protection and similar quality attributes to which end users had become accustomed. Our objective was to certify those very strengths in the HRW wheat cultivar Billings (Reg. No. CV‐1089, PI 656843), released in 2009 by the Oklahoma Agricultural Experiment Station. The cross from which Billings was selected, OK94P597/N566, underscores a historically important dual breeding objective of the Oklahoma State University wheat improvement program: to identify improved fungal disease resistance in, and capitalize on the perceived heterotic pattern among, progeny derived from Great Plains × eastern European crosses. Billings is the bulked descendent of an F4:5 line and was tested as experimental line OK03522. Large kernel size and superior yielding ability reflect Billings' resistance to diseases prevalent in Oklahoma and surrounding states. Its favorable dough strength is expressed as exceptional recovery of isolated gluten fractions from compressive deformation.